The role of Galectin-1 in HIV associated preeclampsia. (March 2020) - Alese, Olutayo Margaret; Moodley, Jagidesa; Naicker, Thajasvarie
Highlights: Gal1 was immunolocalized within Hofbauer cells, cytotrophoblast, syncytial knots and endothelial cells. Immunoexpression of Gal1 was observed irrespective of HIV status. Downregulation of Gal1 in preeclampsia shows its importance in angiogenesis and placentation. Abstract: Objective: In this study, the role of Gal1, a regulatory protein involved in receptor binding and gene transcription within trophoblast cells, in the pathophysiology of HIV associated preeclampsia was determined by immunolocalizing its expression in the placenta of a South African cohort. Study Design: this is an analytical study carried out at the Optics and Imaging Center, Neslon R Mandela School of Medicine, University of KwaZulu-Natal, Durban, South Africa. A hundred and twenty HIV negative or positive, Black African primigrad or multigravid women with pre-eclamptic and normotensive pregnancies were involved in the study. Post-delivery, full thickness of centrally located placental tissue obtained was fixed for immunohistochemistry. The expression of Gal1 was immunolocalized using immunohistochemical assay kit and further quantified with using AxioVision Image analysis software package. Student t -test was used to compare the levels of the analytes while One-way ANOVA was used for comparison across the groups. Results: Gal1 immunoreactivity was observed within the Hofbauer cells, cytotrophoblast, syncytial knots and in the endothelial cells lining blood vessels in both exchange and conducting villi of both normotensive and preeclamptic pregnancies regardless of HIV status. There was a down regulation in Gal1 immunoreactivity in both the exchange and conducting villi of preeclamptic compared to normotensive pregnancies. However, there was no significant effect of HIV infection on Gal1 immunostaining in both villi types. Conclusion: The down regulation of Gal1 in preeclampsia may be due to the inhibition of the MAPK pathway. Since Gal1 influences differentiation and migration, the defective trophoblast invasion in preeclampsia may emanate from its decreased immunoexpression. This highlights the role of Gal1 in angiogenesis and placentation.